(3HUeI GdPcGAGJ GdeJYOOI dOi GddGYHjf aj HYV GdCdYGH GdaQOjI hGdLeGYjIs - (3RhGf(B, (3YGOd cQjes ((3GdEScfOQjI(B:s (3eDSSI YGde GdQjGVI ddfTQ(B,s, 2017)
(3JSYi GdOQGSI GdMGdjI Gdi eYQaI HUeI GdPcGAGJ GdeJYOOI ddGYHjf GdCdYGH GdQjGVjI (B((3GdCdYGH GdaQOjI h GdLeGYjI (B) (3eLGd GdOQGSI, hJMOjO HUeI GdPcGAGJ GdeJYOOI ddGYHjf JHYG dOQLI GdGMJcGc GdHOfj eY GdefGaS aj GdfTGW(B.s
(3GdHHdjhZQGajG U(B.119 (3edGMb (B133(3U(B.s
Keywords: (3GdCdYGH GdaQOjI hGdLeGYjIs; (3GdPcGAs; (3GddGYHjfs